Penerapan Model Pembelajaran PKBP (Pendidikan Kewirausahaan Berbasis Pengalaman) Dalam Meningkatkan Minat Belajar Bisnis - Batsir Podungge (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2020)
Learning model that not only provides insight into the knowledge of concepts only. However, it also provides a real experience that will build skills through a real assignment of entrepreneurship. The result of this research is after applying the Learning Model PKBP (Experience-Based Entrepreneurship Education), students' interest in business learning can increase. While on the second cycle consisting of planning, observation, and reflection action. In this second cycle, the implementation of learning model of PKBP (Experience-Based Entrepreneurship Education), similar to that applied in cycle I, there is only slight difference in this cycle 2 on teaching materials. And the results of the learning model that has been implemented shows an increase in Student Learning Interest of Class XII ATR SMK Negeri Model Gorontalo Tahun Teaching 2016/2017.